Selection in Swimming Training- Theoretical Study - Paweł Eider (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
The aim of this research study is to summarize the notion of preference and selection, which are considered to be the key element of sports training, whatever the discipline.
This review provides a theoretical study on the subject. The introduction section deals with the abovementioned terminology, whereas the main paragraph predominantly discusses the process of preference and selection in swimming.
Pre-school period (6-7 years of age) is the most significant for swimming selection. Such selection should be led by adequately qualified trainers with long-standing experience in professional training of young swimmers. Young swimming candidates should be characterized by higher-level motor skills, which in turn affect the time/efficiency of acquiring new swimming techniques and sport level. In selection process, it is advised/important to utilize tests which predominantly determine the level of specific motor skills such as: speed, strength, agility, motor coordination, suppleness, and so-called 'water feeling'. The above mentioned motor skills play an important role in sport training and sport performance. During selection process, sports team trainers should pay special attention to child's body posture and its length parameters, specifically body's height, length of upper and lower extremities, length of hands and feet, width parameters of the shoulders and chest. First Grade school swimming classes enrollment is also a crucial factor in identifying sport talents. The selection process should be transparent, have clear health, somatic, as well as motoric requirements, which then affect the pace and effectiveness of acquiring swimming skills and sport level.